Arystoteles o starości - Majeran, Roman (Vox Patrum, 2011)
The article discusses Aristotle’s views of old age, which has usually been opposed to Plato’s high esteem thereof. The passage on which this opinion is based is Rhetorics II, 1389b 13 - 1390a 23 which highlights many defects of the ethical character regarded as typical of old age: meanness, mediocrity, diffidence, selfishness. However, this harsh judgment has to be attenuated by considering the context in which Aristotle’s discussion is placed, his objective was description of typical negative features of an audience consisting of old men rather than a balanced and objective discussion and judgment. Aristotle, nevertheless, thinks of the old age and youth as two negative extremes which he opposes to the positive ripeness and perfect balance of mature age. He tends to regard old men as unfit for responsible political tasks and reserves for them the rather symbolic religious functions. In biological terms, he stresses the fact that old age is the time of progressive decadence leading to increasing debility and death. Thus, unlike Plato, who thought of senility as the time of severing the links attaching the soul to the body favorable to the soul’s liberation, Aristotle’s philosophy provided him with no premises for any „praise of old age”.